2017
DOI: 10.1371/journal.pone.0182100
|View full text |Cite
|
Sign up to set email alerts
|

Pituitary adenylate cyclase-activating polypeptide (PACAP) in zebrafish models of nephrotic syndrome

Abstract: Pituitary adenylate cyclase-activating polypeptide (PACAP) is an inhibitor of megakaryopoiesis and platelet function. Recently, PACAP deficiency was observed in children with nephrotic syndrome (NS), associated with increased platelet count and aggregability and increased risk of thrombosis. To further study PACAP deficiency in NS, we used transgenic Tg(cd41:EGFP) zebrafish with GFP-labeled thrombocytes. We generated two models for congenital NS, a morpholino injected model targeting nphs1 (nephrin), which is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…Current evidence suggests that platelets may play a role in VTE pathogenesis and it is well-known that NS may be associated with thrombocytosis (Kerlin et al, 2012a;Wolberg et al, 2015). Meanwhile there are conflicting data regarding the effects of NS on platelet function, which has previously been reported to be both enhanced and impaired during NS (Eneman et al, 2017;Eneman, Levtchenko, van den Heuvel, Van Geet, & Freson, 2016;Svetlov, Moskaleva, Pinelis, Daikhin, & Serebruany, 1999). Our plasma hypercoagulopathy data omit potential contributions from the platelet compartment, although our previously reported whole blood rotational thromboelastometry data correlate well with ETP, suggesting that methods incorporating cellular blood components do not enhance discrimination of hypercoagulopathy (Kerlin, Waller, et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Current evidence suggests that platelets may play a role in VTE pathogenesis and it is well-known that NS may be associated with thrombocytosis (Kerlin et al, 2012a;Wolberg et al, 2015). Meanwhile there are conflicting data regarding the effects of NS on platelet function, which has previously been reported to be both enhanced and impaired during NS (Eneman et al, 2017;Eneman, Levtchenko, van den Heuvel, Van Geet, & Freson, 2016;Svetlov, Moskaleva, Pinelis, Daikhin, & Serebruany, 1999). Our plasma hypercoagulopathy data omit potential contributions from the platelet compartment, although our previously reported whole blood rotational thromboelastometry data correlate well with ETP, suggesting that methods incorporating cellular blood components do not enhance discrimination of hypercoagulopathy (Kerlin, Waller, et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Various pathological condition models have been developed for zebrafish. It has been reported that administration of PACAP could inhibit adriamycin-induced kidney damage and hydrogen peroxide-induced damage of sensory hair cells in zebrafish (34, 35). The results of the distribution of PACAP and PACAP receptors in the zebrafish obtained in this study are also important knowledge for the pathophysiological study of PACAP in zebrafish.…”
Section: Discussionmentioning
confidence: 99%
“…PACAP suppression experiments in zebrafish of Eneman et al revealed that nephrin depletion, a model of nephrotic syndrome is associated with adcyap1a and vip downregulation (76). Using adcyap1a and adcyap1b morpholinos the authors decribed more severe sequelae of nephrin depletion.…”
Section: Urinary Systemmentioning
confidence: 99%
“…Furthermore, nephrotic fishes showed reduced protein expression of PACAP. PACAP morpholinos worsened the change in phenotype induced by adriamycin exposure, which could be attenuated by addition of human PACAP38 (76).…”
Section: Urinary Systemmentioning
confidence: 99%